Change in the Context of Relationships: The Effect of Visitation on Dynamic Risk Change Among Incarcerated Youth - Young, Brae (Youth violence and juvenile justice, 2021)
The consequences of incarceration for juveniles are vast and well-documented. There is some evidence, though, that youth can experience positive transformations, including improvements in dynamic risk during confinement. What we do not yet know is who is the most likely to make such transformations. Using a sample of 7,269 youth housed in residential placement facilities in Florida, this paper examines whether visitation is associated with improvements in dynamic risk during confinement. The results indicate that youth who receive visits and receive them more consistently make greater improvements across nearly all measures of dynamic risk compared to those who do not. Further, there is some evidence that change in dynamic risk mediates the relationship between visitation and recidivism for this group. These findings underscore the importance of continued availability of visitation programs within residential facilities.